Numerical analysis of operating conditions of the transmission pipeline in transient states - Babul, Konrad (Instal, 2020)
Numerical fluid flow simulations, which enable to model the real and transient operating conditions of large-scale industrial installations, make it possible to conduct process risk analysis (HAZOP), multi-variant parametrical economic and technological optimization, as well as selection of the most favorable variant for investment at the design stage. One of the elements of this type of analysis, which are performed for large volumetric flow rates of liquids through long technological and transmission pipelines, may be the selection of appropriate valve closing times, which as a result of risk minimizing associated with the phenomenon of water hammer, will contribute to the use of a lower pressure class of pipelines or avoid the need to install of surge tanks. The article presents analysis of operating conditions of the hydraulic system with a process water transmission pipeline. The subject for numerical verification was the procedure, which includes closure of valves and switching off of the pumping system. The change of operating parameters and geometrical characteristics of the hydraulic system were the source of transients flow of water in the transmission pipeline. Based on the numerical simulations we demonstrated hazards related to the possibility of the phenomenon of water hammer, which lead to sudden increases and drops in pressure in the hydraulic system. The negative influence of backflows inside the transmission pipeline were effectively limited, based on the presented procedure of the valve closing time setting. Verification of operating conditions of the hydraulic system was carried out on the basis of the determined course of static pressure changes in the pipeline and specified limit values of this pressure, which should not be exceeded in analyzed operating conditions of the system.
Keywords: transmission pipeline; numerical modeling; water hammer; fluid flow